The concise guide to becoming an independent consultant - Holtz, Herman (John Wiley & Sons, Inc., 1999)
Packed with expert advice, helpful tips, and industry secrets to successful self-marketing, this guide—an abridged version of the bestselling How to Succeed as an Independent Consultant—gives you the crucial tools and techniques you need to both survive and thrive in this highly competitive field. From founding your business to writing proposals to negotiating fees, The Concise Guide to Becoming an Independent Consultant has complete, up-to-date details on: